Ejaculate-mediated paternal effects: evidence, mechanisms and evolutionary implications. Issue 4 (April 2019) - Evans, Jonathan P; Wilson, Alastair J; Pilastro, Andrea; Garcia-Gonzalez, Francisco
Abstract : Despite serving the primary objective of ensuring that at least one sperm cell reaches and fertilises an ovum, the male ejaculate (i.e. spermatozoa and seminal fluid) is a compositionally complex 'trait' that can respond phenotypically to subtle changes in conditions. In particular, recent research has shown that environmentally and genetically induced changes to ejaculates can have implications for offspring traits that are independent of the DNA sequence encoded into the sperm's haploid genome. In this review, we compile evidence from several disciplines and numerous taxonomic systems to reveal the extent of such ejaculate-mediated paternal effects (EMPEs). We consider a number of environmental and genetic factors that have been shown to impact offspring phenotypes via ejaculates, and where possible, we highlight the putative mechanistic pathways by which ejaculates can act as conduits for paternal effects. We also highlight how females themselves can influence EMPEs, and in some cases, how maternally derived sources of variance may confound attempts to test for EMPEs. Finally, we consider a range of putative evolutionary implications of EMPEs and suggest a number of potentially useful approaches for exploring these further. Overall, our review confirms that EMPEs are both widespread and varied in their effects, although studies reporting their evolutionary effects are still in their infancy.